2022
DOI: 10.3390/molecules27072334
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Non-Targeted Metabolomic Analyses Reveal the Flavonoid Biosynthesis Pathway in Auricularia cornea

Abstract: Flavonoids, which are abundant in plants, are recognized for their antioxidant and anticancer roles in clinical applications. However, little is known about the molecular basis of flavonoid biosynthesis in fungi. In this study, we found that inclusion of leachate of Korshinsk peashrub (Caragana korshinskii) in the fermentation medium increased the total flavonoid content of the edible fungus Auricularia cornea by 23.6% relative to that grown in a control medium. Combined transcriptomic and non-targeted metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Additionally, it suggests the possibility of tailoring mushroom harvest timing to optimize specific flavonoid content according to our needs. Previous studies have annotated the presence of four genes related to flavonoid synthesis in S. baumii (PAL, 4CL, CHI, and IFR) [13] and three in Auricularia cornea (PAL, PPO, and CHI) [12]. These findings suggest that PAL, 4CL, and CHI play crucial roles in initiating flavonoid biosynthesis in both mycelium and fruiting bodies.…”
Section: Key Regulatory Genes For Flavonoid Synthesis In the Fruity B...mentioning
confidence: 68%
See 2 more Smart Citations
“…Additionally, it suggests the possibility of tailoring mushroom harvest timing to optimize specific flavonoid content according to our needs. Previous studies have annotated the presence of four genes related to flavonoid synthesis in S. baumii (PAL, 4CL, CHI, and IFR) [13] and three in Auricularia cornea (PAL, PPO, and CHI) [12]. These findings suggest that PAL, 4CL, and CHI play crucial roles in initiating flavonoid biosynthesis in both mycelium and fruiting bodies.…”
Section: Key Regulatory Genes For Flavonoid Synthesis In the Fruity B...mentioning
confidence: 68%
“…Research on plant flavonoid biosynthesis has identified and characterized the roles of F3′H and DFR in regulating flavonoid production. For example, the importance of F3′H in the accumulation of flavonoids in various plant species, including apples (malus Previous studies have annotated the presence of four genes related to flavonoid synthesis in S. baumii (PAL, 4CL, CHI, and IFR) [13] and three in Auricularia cornea (PAL, PPO, and CHI) [12]. These findings suggest that PAL, 4CL, and CHI play crucial roles in initiating flavonoid biosynthesis in both mycelium and fruiting bodies.…”
Section: Key Regulatory Genes For Flavonoid Synthesis In the Fruity B...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, not every mushroom can be cultivated under laboratory conditions; however, although obtaining fruiting bodies in vitro can sometimes be impossible, the cultivation of mycelia seems to be easier and more successful. Meng et al [79] recently published interesting results from transcriptomic and metabolomic analyses of flavonoid-biosynthesis-related pathways in cells of the edible mushroom Auricularia cornea cultivated on media with different substrates. They analyzed the expression of genes engaged in flavonoid biosynthesis and applied nontargeted metabolomic analysis using an LC-MS system to find metabolites of the flavonoid biosynthesis pathway.…”
Section: Current Achievements and Future Prospectsmentioning
confidence: 99%
“…The researchers proved, among others, that metabolites connected to coumarin, phenylpropanoid and isoflavonoid biosynthesis pathways were produced in A. cornea, and especially interesting was the detection of the isoflavones biochanin A, formononetin and coumestrol. They also revealed that the addition of the leachate of Korshinsk peashrub (Caragana korshinskii) to the complete yeast medium (CYM) could increase the flavonoid content by up to 23.6% in comparison with the amount obtained after the cultivation of A. cornea on the control CYM medium [79]. Recently, studies concerning flavonoid presence and synthesis in Sanghuangporus baumii cells were published by Wang et al [80].…”
Section: Current Achievements and Future Prospectsmentioning
confidence: 99%